O custos legis retórico : a desconstrução do fiscal da lei no processo civil brasileiro - Lessa, Eduardo Henrique Borba (2011)
This study aims to investigate the use of the rhetoric of the public prosecutor in his role as custos legis in civil proceedings, and, as well as the deconstruction of that action, which is being observed today, starting a movement that takes shape within the institution. As in all academic work, which attempts to find an answer to a given question or the solution to a given problem, this thesis aims to investigate the founding elements of the rant of the custos legis on civil procedure and investigate arguments justifying a tendency to add a second plane that performance, comparing to these aspects to the story and the legal system in force in the country. In preparing the study explored the following themes: prosecutors and its history, the world and the country in order to understand the institution and the north constitutional constrain, the actions of the prosecutor in the judicial process, focusing on custos legis action in civil proceedings, and internal movement of deconstruction that performance under the canopy of an alleged atrophy in the face of collective action; Aristotelian rhetoric, historical aspects and characteristics in order to assert the nature of rhetorical discourse of the custos legis, its relevance, and how it materializes in the civil lawsuit. We come thus to the conclusion that the rant of the custos legis in Brazilian civil procedure laws is the responsibility of the institution immovable, without there being the arguments to the contrary, is the historical perspective, either by their unsustainable before the legal system as a whole including the Federal Constitution